The effectiveness of the REAL™, a school-based, virtual reality-integrated social emotional learning intervention to promote mental health for early Malaysian adolescents - Baharuddin, Aimi Nur Athira Putri; Nik Jaafar, Nik Ruzyanei; Ibrahim, Normala; Ahmad Badayai, Abdul Rahman; Mohd Salleh Sahimi, Hajar; Mohamad Kamal, Nurul Ain; Ismail, Nur Husna; Salwana, Ely; Abdullah, Mohd Pilus; Ahmad Zamzuri, Mohd ‘Ammar Ihsan (Elsevier, 2025)
Background: The REAL™ module was developed to impart social and emotional learning (SEL) skills to early Malaysian adolescents using virtual reality (VR) components at school within the local social and cultural dynamics. This study aimed to evaluate the effectiveness of the intervention in improving 1) emotional regulation (ER) skills and 2) depression and anxiety in adolescents attending lower secondary schools in Malaysia. Methods: This randomized controlled trial study was conducted from February 2023 to November 2023. A total of 226 participants aged 13 and 14 years old from lower secondary school students were recruited from four secondary schools selected by multistage cluster sampling in Selangor, Malaysia. Data were collected across four-time points (T0: baseline, T1: immediate post-test, T2: three-month post-test, and T3: six-month post-test) via a locally translated and validated set of questionnaires, including The Difficulties in Emotion Regulation Scale (DERS) for the emotional regulation score, Beck Depression Inventory (BDI) for depression scores and Beck Anxiety Inventory for anxiety scores. A repeated-measures ANCOVA was performed to evaluate the effect of the intervention versus the control group on emotional regulation scores, depression scores, as well as anxiety scores. Results: A significant main effect of the group intervention was observed for emotional regulation (F (1, 223) = 20.05, p < 0.001), depression (F (1, 223) = 51.16, p < 0.001), and anxiety (F (1, 223) = 32.75, p < 0.001). The intervention group showed a sustained reduction for all domains compared to the control group, particularly at time T3. These findings reflect differences in outcomes between the intervention and control groups. Conclusion: This study showed that the REAL™ intervention improved adolescents' emotional regulation skills and reduced their depression and anxiety scores. The program features a feasible school-based delivery using a socioculturally sensitive module integrated with VR components. This could facilitate adolescents’ learning engagement and resonate with their sociocultural context, making the skills relatable and attainable.